Coastal Vulnerability Assessment Based on Coastal Vulnerability Index (CVI) on the Coastal Area of Kolaka Regency, Southeast Sulawesi, Indonesia - Kharisma, Gaby; Triani, Triani; Ulfa, Azura; Adriadi Ghiffari, Rizki; Anjas Sari, Hermis (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The purpose of this paper is to investigate vulnerability assessments along the coastal area and small island of Kolaka Regency, Southeast Sulawesi, Indonesia. This paper used spatial analysis to estimate the Coastal Vulnerability Index (CVI). An assessment of CVI was carried out using eight parameters to build into five categories, with very low to very high category vulnerability. Coastal vulnerability in the Kolaka coastal area varies from a very low to a very high category. Hence, this study suggests that policymakers need to make a long-term plan for local coastal zones, and they should prioritize a precision disaster-based analysis to minimize the damage caused by the disaster in the future.